The description of the tiger beetle larvae of Cosmodela aurulenta (Fabricius, 1801)(Coleoptera, Cicindelidae) - Putchkov, Alexander V.; Markina, Tetiana Yu. (Zootaxa, 2020)
All larval instars of the tiger beetle species Cosmodela aurulenta aurulenta (Fabricius, 1801) which is the type species of the genus Cosmodela Rivalier, 1961 are described and illustrated here for the first time, based on material from Bali Island (Indonesia). A brief review of habitat preferences and ecology for adults and larvae of Cosmodela aurulenta are provided. Differences between C. aurulenta and C. batesi (Fleutiaux, 1893) and allied Palaearctic genera of the subtribe Cicindelina are discussed. The preliminary key of known larvae of relevant genera and subgenera of the Oriental Region is given.